Experimental jaw-muscle pain has a differential effect on different jaw movement tasks - Sae-Lee, Daraporn; Whittle, Terry; Peck, Chris C; Forte, Anna R C; Klineberg, Iven J; Murray, Greg M (Journal of orofacial pain, 2008)
To determine the effects of experimental jaw-muscle pain on jaw movements. Mandibular mid-incisor point was tracked in 22 asymptomatic subjects during standardized (at 2.2 mm/s) protrusion, contralateral excursion, and open jaw movements, as well as free, right-sided chewing and chewing standardized for timing (900 ms/cycle). Tonic infusion of 4.5% hypertonic saline into the right masseter muscle maintained pain intensity between 30 and 60 mm on a 100-mm visual analog scale. Subjects performed tasks in 3 sessions on the same experimental day: control condition (baseline trials), test condition 1 (during hypertonic or 0.9% isotonic saline infusion), and test condition 2 (during isotonic or hypertonic saline infusion). In comparison with control, there were no significant effects of hypertonic saline infusion on amplitude or velocity for protrusion or contralateral jaw movements or on velocity for jaw opening. Jaw-opening amplitude was significantly smaller in comparison with control during hypertonic, but not isotonic, saline infusion. During free but not standardized chewing, subjects chewed faster and exhibited larger amplitude gapes during hypertonic and isotonic infusion in comparison with control. Therefore, it was unlikely that pain had an effect on the kinematic parameters of jaw movement during free chewing. Qualitatively, individual subject data revealed considerable variability in the effects of hypertonic saline on movement parameters, which suggests that the effect of pain on jaw movement may not be uniform between individuals. The data indicate that the effect of pain on jaw movement may vary with the task performed.